Magnetic Resonance Imaging-guided Active Surveillance Without Annual Rebiopsy in Patients with Grade Group 1 or 2 Prostate Cancer: The Prospective PROMM-AS Study - Birte Valentin; Christian Arsov; Tim Ullrich; Rouvier Al-Monajjed; Matthias Boschheidgen; Boris A. Hadaschik; Francesco Giganti; Markus Giessing; Cristina Lopez-Cotarelo; Irene Esposito; Gerald Antoch; Peter Albers; et al. (European Urology Open Science, 2024)
Background: Multiparametric magnetic resonance imaging (mpMRI) may allow patients with prostate cancer (PC) on active surveillance (AS) to avoid repeat prostate biopsies during monitoring. Objective: To assess the ability of mpMRI to reduce guideline-mandated biopsy and to predict grade group upgrading in patients with International Society of Urological Pathology grade group (GG) 1 or GG 2 PC using Prostate Cancer Radiological Estimation of Change in Sequential Evaluation (PRECISE) scores. The hypothesis was that the AS disqualification rate (ASDQ) rate could be reduced to 15%. Design, setting and participants: PROMM-AS was a prospective study assessing 2-yr outcomes for an mpMRI-guided AS protocol. A 12 mo after AS inclusion on the basis of MRI/transrectal ultrasound fusion-guided biopsy (FBx), all patients underwent mpMRI. For patients with stable mpMRI (PRECISE 1–3), repeat biopsy was deferred and follow-up mpMRI was scheduled for 12 mo later. Patients with mpMRI progression (PRECISE 4–5) underwent FBx. At the end of the study, follow-up FBx was indicated for all patients. Outcome measurements and statistical analysis: We calculated the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for upgrading to GG 2 in the GG 1 group, and to GG 3 in the GG 2 group on MRI. We performed regression analyses that included clinical variables. Results and limitations: The study included 101 patients with PC (60 GG 1 and 41 GG 2). Histopathological progression occurred in 31 patients, 18 in the GG 1 group and 13 in the GG 2 group. Thus, the aim of reducing the ASDQ rate to 15% was not achieved. The sensitivity, specificity, PPV, and NPV for PRECISE scoring of MRI were 94%, 64%, 81%, and 88% in the GG 1 group, and 92%, 50%, 92%, and 50%, respectively, in the GG 2 group. On regression analysis, initial prostate-specific antigen (p < 0.001) and higher PRECISE score (4–5; p = 0.005) were significant predictors of histological progression of GG 1 PC. Higher PRECISE score (p = 0.009), initial Prostate Imaging-Reporting and Data System score (p = 0.009), previous negative biopsy (p = 0.02), and percentage Gleason pattern 4 (p = 0.04) were significant predictors of histological progression of GG 2 PC. Limitations include extensive MRI reading experience, the small sample size, and limited follow-up. Conclusions: MRI-guided monitoring of patients on AS using PRECISE scores avoided unnecessary follow-up biopsies in 88% of patients with GG 1 PC and predicted upgrading during 2-yr follow-up in both GG 1 and GG 2 PC. Patient summary: We investigated whether MRI (magnetic resonance imaging) scores can be used to guide whether patients with lower-risk prostate cancer who are on active surveillance (AS) need to undergo repeat biopsies. Follow-up biopsy was deferred for 1 year for patients with a stable score and performed for patients whose score progressed. After 24 months on AS, all men underwent MRI and biopsy. Among patients with grade group 1 cancer and a stable MRI score, 88% avoided biopsy. For patients with MRI score progression, AS termination was correctly recommended in 81% of grade group 1 and 92% of grade group 2 cases.